Selected Works of Peter J. Bickel - Fan, Jianqing; Ritov, Ya'acov.; Wu, C.F. Jeff.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This volume presents selections of Peter J. Bickel$1 (Bs major papers, along with comments on their novelty and impact on the subsequent development of statistics as a discipline. Each of the eight parts concerns a particular area of research and provides new commentary by experts in the area. The parts range from Rank-Based Nonparametrics to Function Estimation and Bootstrap Resampling. Peter$1 (Bs amazing career encompasses the majority of statistical developments in the last half-century or about half of the entire history of the systematic development of statistics. This volume shares insights on these exciting statistical developments with future generations of statisticians. The compilation of supporting material about Peter$1 (Bs life and work help readers understand the environment under which his research was conducted. The material will also inspire readers in their own research-based pursuits. This volume includes new photos of Peter Bickel, his biography, publication list, and a list of his students. These give readers a more complete picture of Peter Bickel as a teacher, a friend, a colleague, and a family man.s
Foreword by Peter J. Bickel -- Preface -- Biography -- Publications -- Ph.D. Students -- Photos -- Rank-Based Nonparametrics -- Robust Statistics -- Asymptotic Theory -- Functional Estimation -- Adaptive Estimation -- Bootstrap Resampling -- High-Dimensional Statistics -- Miscellaneous.
Keywords: Statistics; Mathematical statistics; Statistics; Statistical Theory and Methods; Statistics, general